Examining the Role of DNA Methylation in Transcriptomic Plasticity of Early Stage Sea Urchins: Developmental and Maternal Effects in a Kelp Forest Herbivore - Strader, Marie E.; Kozal, Logan C.; Leach, Terence S.; Wong, Juliet M.; Chamorro, Jannine D.; Housh, Madeline J.; Hofmann, Gretchen E. (Frontiers in Marine Science, 2020)
Gene expression plasticity can confer physiological plasticity in response to the environment. However, whether epigenetic marks contribute to the dynamics of gene expression is still not well described in most marine invertebrates. Here, we explored the extent and molecular basis of intra- and intergenerational plasticity in the purple sea urchin, Strongylocentrotus purpuratus, by examining relationships between changes in DNA methylation, transcription, and embryo spicule length. Adult urchins were conditioned in the lab for four months to treatments that represent upwelling (~1100μatm pCO2, 13 °C) and non-upwelling conditions (~500μatm pCO2, 17 °C). Embryos spawned from conditioned adults were reared in either the same adult treatment or the reciprocal condition. Maternal conditioning resulted in significantly differentially methylated CpG sites and differential gene expression in the larvae, despite no evidence of maternal effects on embryo spicule length. In contrast, conditions experienced during development resulted in significant differences in larval spicule length. Intragenerational plasticity in spicule length was strongly correlated to transcriptomic plasticity, despite low levels of intragenerational plasticity in CpG methylation. We find plasticity in DNA methylation and gene expression in response to different maternal environments and these changes have similarities across broad functional groups of genes; yet exhibit little overlap on a gene-by-gene basis. Our results suggest that different forms of environmentally induced plasticity are observable across different time scales and that DNA methylation dynamics may be uncoupled from fast transcriptional responses to the environment and whole organism traits. Overall, this study illuminates the extent to which environmental differences can induce both intra- and intergenerational phenotypic plasticity in a common kelp forest herbivore.